Damage evolution of biodegradable magnesium alloy stent based on configurational forces. (9th June 2021) - Wang, Rong; Yuan, Zhongbo; Li, Qun; Yang, Bo; Zuo, Hong
Abstract: Magnesium alloy has attracted most of the recent attention as a candidate for stent material due to their biocompatible and biodegradable nature. However, their corrosion behavior in the human body is still a major issue in research today. In this paper, a strategy to simulate damage evolution in biodegradable magnesium alloy stent is given by introducing a configurational damage model. In the framework of continuum thermodynamics, one can characterize the development and evolution of local damage of materials by establishing internal variables in phenomenological method. We believe that corrosion can damage alloy in two different ways: surface corrosion and stress corrosion. Surface corrosion is described using uniform damage, when the structure is exposed in a corrosion environment; Configurational force is used to describe stress corrosion when the structure is exposed in a stimulating environment. We then select global damage and radial resistance force to perform the changes of macroscopic mechanical properties during stent degradation. Finally, the well performance of the proposed model is demonstrated through several numerical examples. This model has the potential to assist stent design and development in the future.